A suitable design of metal hydride cartridge for a fuel cell assisted bicycle in consideration of heat transfer performance. Issue 1 (1st June 2022) - Hara, Daisuke; Miao, Shan; Shimogawa, Junnosuke; Katayama, Noboru; Dowaki, Kiyoshi
Abstract: Metal hydrides (MHs) can store hydrogen produced from biomass at low pressure and high volumetric energy density. However, the endothermic reaction that occurs during hydrogen discharge decreases the hydrogen flow rate, which prevents the generation of sufficient power for fuel cell (FC) devices. Because a previous study reported that the hydrogen capacity of MHs would drop by approximately 20% due to the hydrogen sulfide contained in hydrogen from biomass, the utilizable amount of hydrogen in MHs should be enhanced. In this study, MH utilization for an FC-assisted bicycle in consideration of waste heat recovery from MH to FC was investigated. The results show that the MH-based hydrogen storage system can weigh 8 kg or lower for the FC bicycle to travel twice the distance of a lithium-ion-battery-derived bicycle. Using the mathematical model of hydrogen discharge from the MH, the heat transfer of a small MH cartridge for the FC bicycle was investigated. The center of the cartridge cooled by approximately 20 K from the initial temperature, indicating the necessity of heat injection into the MH cartridge even if the initial and boundary temperatures were high. It was also concluded that 83% of the hydrogen charged in the MH could be utilized to maintain the hydrogen flow rate to run a 220 W FC.